Program Khazanah Trans7 Sebagai Media Dakwah dalam Meningkatkan Pemahaman Keagamaan - Fitri, Nurul (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2014)
This study examines the effectiveness of Trans7’s Khazanah as a medium of Islamic preaching among Mulya Bhakti residents in Cimahi. Using a descriptive qualitative approach and the Stimulus–Organism–Response (S–O–R) theory, the study finds that Khazanah effectively influences viewers cognitively, affectively, and psychomotorically. The program broadens Islamic understanding, evokes spiritual calmness, and encourages positive religious behavior within families. Moreover, it creates a space for spiritual dialogue, transforming television into a medium of reflection for urban audiences. The study concludes that media-based dakwah remains relevant when delivered aesthetically, humanistically, and contextually.